Evaluation of Secondary and Micronutrients for Soybean Production in Kansas - M. N. Gutierrez; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2015)
Study of secondary and micronutrients is growing because of their potential contribution to yield increases. The objective of this study was to evaluate soybean response to secondary and micronutrient fertilizer application to maximize yields. A randomized complete block design was employed with four replications at five locations during 2013 and five locations in 2014. Treatments consisted of an unfertilized control; micronutrient fertilizer as individual nutrients for boron, copper, manganese, sulfur, and zinc; and a mix of these nutrients using two different placements (dry broadcast and liquid band). Soil samples were collected prior to planting and after harvest. Soybean trifoliates were collected at R2–R3 growth stage and analyzed for the micronutrients evaluated in this study. At harvest, nutrient concentration was analyzed in the seed, and yield was calculated at 13% moisture. No significant difference was found in yields between treatments by location or across locations. Results from tissue and grain analysis showed significant treatment effects on zinc concentrations across locations.
Keywords: micronutrient; soybean; tissue analysis